THE EFFECTS OF PUBLIC WORKS PROGRAMS – THE CASE OF THE SLOVAK REPUBLIC - Dováľová, Gabriela; Hvozdíková, Veronika (European Scientific Journal, ESJ, 2014)
The long-term unemployment in Slovakia belongs traditionally to the highest group of such in the EU and represents one of the most serious problems for the Slovak labour market. More than one half of the unemployed are those with the lowest level of education, this paper thus focuses on the current situation of the low-qualified workforce as well as on the assessment of the effects of activation policy programs in Slovakia which are aimed at stimulating the growth of labour demand, especially for those who belong to the most disadvantaged groups on the labour market. However, international experience (e. g. Kuddo, 2009) points to the fact that, when taking into account the low efficiency and cost ineffectiveness of this measure, it simply turns into a ―safety net‖ supporting the income of individuals and decreasing the poverty rate among individuals disadvantaged in the labour market. The studies also uncovered that in the long run the impact of such measures on employment is in many cases negative, defining stigmatization of the program's participants as one of the reasons – the persons having participated in the programs are automatically considered as less productive, which decreases the probability of their job placement. The efficiency and cost effectiveness of these programs may be influenced considerably by the so-called lock-in effect which means that program participants may receive less job offers while attending the program as well as that they may be less motivated to seek for job openings.